Ultrasound‐Guided Peripheral Intravenous Catheter Training Results in Physician‐Level Success for Emergency Department Technicians - Duran-Gehring, Petra; Bryant, Laurie; Reynolds, Jennifer A.; Aldridge, Petra; Kalynych, Colleen J.; Guirgis, Faheem W. (Journal of ultrasound in medicine, 2016)
Objectives To report our success and complication rates with emergency department (ED) technician–performed ultrasound (US)‐guided peripheral intravenous (IV) catheter placement and to compare our results to similar studies in the literature. Methods We conducted a retrospective review of a prospective database of patients who underwent US‐guided peripheral IV catheter placement attempts for clinical care in the ED. All patients meeting difficult IV access criteria who had a US‐guided peripheral IV catheter placement attempted by a trained ED technician were included. Average attempts per success and overall success rates were compared to similar published studies. Results There were 830 participants, with an overall success rate of ED technician– performed US‐guided peripheral IV catheter placement of 97.5%. Clinicians categorized 82.6% of participants as having difficult IV access and reported that in 46.5%, a central venous catheter would have been necessary if the US‐guided peripheral IV catheter failed. Of successful catheter attempts, 86.8% were placed on the first attempt; 11.6% were placed on the second attempt; and 1.6% were placed on the third attempt. For this study, the average number of attempts per success was 1.15 (95% confidence interval, 1.12–1.18), which was lower than in 6 other published studies, ranging from 1.27 to 1.70. The overall success rate of our ED technician‐performed attempts was 0.970 (95% confidence interval, 0.956–0.983), which was higher than that reported in previous ED technician studies (0.79–0.80), and closer to that reported for physicians or nurses (0.87–0.97). The arterial puncture complication rate was 0.8%, which was also lower than in other published studies (1.25%–9.80%). Conclusions With brief but comprehensive training, ED technicians can successfully obtain US‐guided peripheral IV catheter access in patients with difficult IV access.